Bimetal supported CoLa-FZSM-5 catalyst as well as preparation method and application thereof

Through acid etching and metal loading treatment of ZSM-5, the CoLa-FZSM-5 catalyst is formed, which solves the problems of diffusion limitation in lignite pyrolysis and low yield of light aromatic hydrocarbons, and improves the yield of light aromatic hydrocarbons and catalyst activity. , achieving a more efficient lignite pyrolysis process.

CN119259108APending Publication Date: 2025-01-07UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411385925.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

Smart Images

  • Figure CN119259108A_ABST
    Figure CN119259108A_ABST
Patent Text Reader

Abstract

The invention discloses a bimetallic supported CoLa-FZSM-5 catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalysts. The preparation method of the bimetallic supported CoLa-FZSM-5 catalyst comprises the following steps: (1) dispersing a ZSM-5 molecular sieve into an acidic etching solution, stirring until the ZSM-5 molecular sieve is pasty, washing until the ZSM-5 molecular sieve is neutral, and draining water; performing calcination, cooling and drying to obtain FZSM-5; and (2) adding FZSM-5 into the mixed solution, stirring, dipping, calcining, cooling and drying to obtain the catalyst. The invention also discloses the application of the bimetallic supported CoLa-FZSM-5 catalyst in catalysis of lignite pyrolysis. When the bimetallic loaded CoLa-FZSM-5 catalyst is applied to lignite pyrolysis, the activation energy required for forming volatile components by light fragments in a coal molecular structure can be reduced, the mass transfer efficiency in the lignite pyrolysis process can be improved, the yield of light aromatic hydrocarbons can be effectively improved, and the bimetallic loaded CoLa-FZSM-5 catalyst has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a bimetallic supported CoLa-FZSM-5 catalyst and a preparation method and application thereof, belonging to the technical field of catalysts. Background Art

[0002] Lignite is a brown-black, dull, low-rank coal with a very low degree of coalification. It usually has low calorific values, high oxygen content and high moisture content, which greatly limits the utilization of lignite. In view of the low quality of lignite, lignite quality improvement technologies including coal pyrolysis, coal gasification and coal liquefaction have been widely studied. Among them, lignite pyrolysis is an important way to achieve clean conversion of lignite and a prerequisite for lignite gasification. It plays an important role in the gasification, liquefaction and combustion of lignite. Lignite can produce various aromatic hydrocarbons through cracking, reforming, isomerization and aromatization, especially light aromatic hydrocarbons (LAs) such as benzene (B), toluene (T), ethylbenzene (E), xylene (X) and naphthalene (N). BTEXN has a high utilization value and has been widely used in the synthesis and production of various chemical products. Normally, affected by the properties of coal and the pyrolysis process, the output of coal pyrolysis tar accounts for about 2.5% to 4.0% of the raw coal mass, of which heavy components with a boiling point above 360°C usually account for 50% of the total tar. These heavy components are viscous and have poor fluidity, and may be deposited on pipelines and block downstream equipment, leading to serious operational problems. It can be seen that the output of light aromatics in the traditional pyrolysis process is not high, and many studies have shown that catalytic pyrolysis can convert heavy components into light aromatics and gases under moderate conditions, thereby increasing the value of lignite pyrolysis products.

[0003] ZSM-5 molecular sieve is a zeolite molecular sieve containing organic amine cations. ZSM-5 is very active in catalytic chemistry. Due to its accessibility to acid sites and two-dimensional channel-like void systems, it can form molecular-scale pores or channels, has high skeleton stability, and has strong selectivity. Therefore, ZSM-5-based catalysts are widely used in the pyrolysis conversion of lignite or biomass. However, as a porous zeolite-type material, traditional ZSM-5 has inherent diffusion limitations, which results in some high molecular weight oxides being unable to pass through the catalyst micropores. These substances will aggregate on the surface to form coke, thereby reducing the catalyst activity and affecting the coal pyrolysis selectivity. Therefore, many scholars have conducted extensive research on the introduction of secondary pores such as mesopores and micropores in ZSM-5. At present, there are no literature reports on the etching of ZSM-5 using HF and NH4F solutions, bimetallic Co-La-loaded ZSM-5 catalysts, and their catalytic pyrolysis of lignite. Summary of the invention

[0004] In view of the above-mentioned prior art, the present invention provides a bimetallic supported CoLa-FZSM-5 catalyst, and a preparation method and application thereof.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing a bimetallic supported CoLa-FZSM-5 catalyst comprises the following steps:

[0007] (1) Dispersing ZSM-5 molecular sieve in an acidic etching solution, stirring at room temperature until it becomes a paste (about 8 minutes), rinsing with deionized water until it becomes neutral, and controlling the water; then placing the molecular sieve in a muffle furnace, heating it to 540-560° C. at a heating rate of 4-6° C. / min in an air environment and maintaining it for 1.5-2.5 hours, cooling and drying, and obtaining a graded molecular sieve, which is labeled as FZSM-5;

[0008] The acidic etching solution is composed of an HF aqueous solution and NH4F dissolved therein, wherein the concentration of the HF aqueous solution is 0.4-0.6 mol / L, preferably 0.5 mol / L, and the concentration of NH4F is 130-200 g / L, preferably 166.7 g / L;

[0009] (2) adding FZSM-5 to the mixed solution, stirring at 35-45° C. for 2.5-3.5 h, and immersing under dry conditions until the water is completely evaporated to obtain a dry solid; then placing in a muffle furnace, calcining at 580-620° C. for 3-5 h in an air environment, cooling and drying to obtain a bimetallic supported CoLa-FZSM-5 catalyst, wherein the loading amount of Co is 1%-10% (weight percentage), preferably 3%-5%, more preferably 4%, and the loading amount of La is 1%-10% (weight percentage), preferably 3%-5%, more preferably 4%;

[0010] The mixed solution is composed of Co(NO3)2·6H2O, La(NO3)3·6H2O and water. The dosage ratio of FZSM-5, Co(NO3)2 and La(NO3)3 can be calculated according to the final required metal loading amount.

[0011] Furthermore, in the step (1), the ZSM-5 molecular sieve is pretreated as follows: the ZSM-5 molecular sieve is placed in a muffle furnace, calcined at 580-620° C. in an air environment for 3-5 hours (to remove impurities and moisture), cooled, dried, and set aside.

[0012] Furthermore, in the step (1), the SiO2 / Al2O3 ratio of the ZSM-5 molecular sieve is 25.

[0013] Furthermore, in the step (1), the temperature is increased to 550° C. at a heating rate of 5° C. / min and maintained for 2 h.

[0014] Furthermore, in the step (2), FZSM-5 is added to the mixed solution, stirred at 40°C for 3 hours, and then immersed in a dry state at 105°C until the water is completely evaporated to obtain a dry solid; then placed in a muffle furnace and calcined at 600°C for 4 hours in an air environment.

[0015] A bimetallic supported CoLa-FZSM-5 catalyst is prepared by using the above preparation method.

[0016] The bimetallic supported CoLa-FZSM-5 catalyst is used in catalyzing the pyrolysis of lignite.

[0017] The bimetallic supported CoLa-FZSM-5 catalyst is used to improve the yield of light aromatic hydrocarbons during pyrolysis of lignite, and further, the light aromatic hydrocarbons are selected from any one or more of benzene, ethylbenzene and xylene.

[0018] The bimetallic supported CoLa-FZSM-5 catalyst of the present invention uses an acidic solution to dealuminate and delaminate ZSM-5 during preparation, introduces mesoporous and macroporous structures, and improves the pore structure of the molecular sieve; and on this basis, metal elements are loaded so that the metal elements can enter the pores of the molecular sieve, thereby improving the accessibility of the metal elements. Compared with the disadvantage that the traditional loading of metal elements only allows the metal elements to attach to the surface, the present invention pre-places the acidic solution treatment process, which can improve the pore size of ZSM-5, allowing the metal elements to penetrate into the interior of the zeolite, thereby improving the landing point of the metal elements.

[0019] The bimetallic supported CoLa-FZSM-5 catalyst of the present invention, when applied to lignite pyrolysis, can reduce the activation energy required for light fragments in the coal molecular structure to form volatiles, improve the mass transfer efficiency during lignite pyrolysis, and effectively increase the yield of light aromatics. The present invention also uses the main graph method to determine the reaction mechanism function. When the conversion rate α is less than 0.15, the lignite pyrolysis process follows the nucleation model. As the conversion rate increases, the lignite pyrolysis process follows the reaction order and nucleation model.

[0020] The bimetallic supported CoLa-FZSM-5 catalyst of the present invention has good application prospects and is of great value and significance for the research and industrial application of lignite pyrolysis.

[0021] Various terms and phrases used herein have the general meanings that are well known to those skilled in the art. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 : Schematic diagram of XRD results of zeolite molecular sieve catalyst.

[0023] Figure 2 : Schematic diagram of N2 adsorption and desorption isotherms of zeolite molecular sieve catalyst.

[0024] Figure 3 : Schematic diagram of the pore size distribution of zeolite molecular sieve catalyst.

[0025] Figure 4 : SEM and TEM images of zeolite molecular sieve catalysts, including: (a) SEM micrograph of ZSM-5; (b) TEM image of FZSM-5; (c) TEM image and energy spectrum image of CO-FZSM-5; (d) TEM image and energy spectrum image of LA-FZSM-5; (e) TEM image and energy spectrum image of Cola-FZSM-5.

[0026] Figure 5 : Schematic diagram of NH3-TPD spectrum of zeolite molecular sieve catalyst.

[0027] Figure 6: TG curves of pyrolysis of each zeolite molecular sieve catalyst mixed with lignite in a ratio of 1:1.

[0028] Figure 7 : DTG curves of pyrolysis of each zeolite molecular sieve catalyst mixed with lignite in a ratio of 1:1.

[0029] Figure 8 : TG curves and DTG curves of non-catalytic pyrolysis of lignite at different heating rates (5, 10, 20 and 40℃ / min).

[0030] Fig. 9 : DTG curves of lignite catalytic pyrolysis at different heating rates (5, 10, 20 and 40℃ / min).

[0031] Fig.10 : Schematic diagram of the effect of various zeolite molecular sieve catalysts on the selectivity of lignite pyrolysis products, wherein (a) is the ion chromatogram; (b) is the relative content of volatile products; and (c) is the product yield.

[0032] Fig.11 : The calculation process of dynamic analysis.

[0033] Fig.12 : Fitting straight lines of the catalytic and non-catalytic pyrolysis kinetics of lignite calculated using four equal conversion rate methods: Starink, Friedman, FWO and KAS. Among them, (a), (b), (c), (d) are non-catalytic pyrolysis (Starink, Friedman, FWO and KAS, respectively); (e), (f), (g), (h) are catalytic pyrolysis of CoLa-FZSM-5 (Starink, Friedman, FWO and KAS, respectively).

[0034] Fig.13 : Activation energy calculated using Starink, Friedman, FWO and KAS models versus conversion rate, where (a), (b), (c), and (d) are Starink, Friedman, FWO, and KAS respectively.

[0035] Fig.14 : Experimental curves and standard curves of non-catalytic pyrolysis and catalytic pyrolysis of lignite, wherein (a) is non-catalytic pyrolysis; (b) is catalytic pyrolysis.

[0036] Fig.15 : Schematic diagram of HF and NH4F mixed acid solution etching and metal loading ZSM-5 process. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with the embodiments. However, the scope of the present invention is not limited to the following embodiments. It will be appreciated by those skilled in the art that various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention.

[0038] The instruments, reagents, and materials involved in the following examples, unless otherwise specified, are all conventional instruments, reagents, and materials available in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following examples, unless otherwise specified, are all conventional experimental methods and detection methods available in the prior art.

[0039] Example 1 Modification of ZSM-5 molecular sieve

[0040] Here are the steps:

[0041] (1) Take a ZSM-5 molecular sieve with a SiO2 / Al2O3 ratio of 25 (which can be purchased on the conventional market; the ZSM-5 commercial micron-sized zeolite molecular sieve used in the present invention is purchased from the catalyst factory of Nankai University), place it in a muffle furnace, and calcine it at 600°C for 4 hours in an air environment to remove impurities and moisture when the catalyst leaves the factory, cool it, dry it, and store it for future use.

[0042] (2) Disperse 5 g of ZSM-5 molecular sieve in 150 ml of acidic etching solution, stir at room temperature for 8 min, rinse with deionized water until neutral, place the paste molecular sieve in a forced air drying oven, and control the moisture under drying conditions of 105 ° C; then place the molecular sieve in a muffle furnace, and heat it to 550 ° C at a heating rate of 5 ° C / min in an air environment. After reaching the terminal temperature, keep it for 2 h, cool it naturally, and dry it to obtain a graded molecular sieve, which is marked as FZSM-5.

[0043] The acidic etching solution is prepared by the following method: dissolving 25 g of NH4F in a 0.5 mol / L HF aqueous solution, and then making the volume to 150 ml with the 0.5 mol / L HF aqueous solution.

[0044] (3) Take 3 portions of FZSM-5 (5 g each) and add them to Co(NO3)2·6H2O solution (250 ml), La(NO3)3·6H2O solution (250 ml), and mixed solution (mixed solution consisting of Co(NO3)2·6H2O, La(NO3)3·6H2O and water) (250 ml) (Note: the content of solute in each solution is calculated based on the loading amount of 8%), stir at 40°C for 3 h, and then place in a forced air drying oven for 1 h. The samples were immersed in a dry environment at 05°C until the water was completely evaporated to obtain a dry solid (about 12 hours); then placed in a muffle furnace, calcined at 600°C for 4 hours in an air environment, naturally cooled and dried to obtain metal-loaded molecular sieves, which were named Co-FZSM-5, La-FZSM-5, and CoLa-FZSM-5, respectively, with a loading amount of 8 wt% (for Co-La-FZSM-5, 4 wt% Co and 4 wt% La); the molecular sieves were placed in a sealed container for future use.

[0045] Experiment 1 Catalyst Characterization

[0046] (1) XRD analysis

[0047] Using Malvern Panalytical X'Pert 3 The crystal structure of the catalyst was characterized by an X-ray diffractometer (XRD). The configuration conditions of this instrument are Cu Kα radiation (1.5418nm), voltage 40kV, current 40mA. The instrument scans 2θ from 5° to 50°, and the scanning rate is 10° / min.

[0048] The XRD results of the zeolite molecular sieve catalysts (ZSM-5, FZSM-5, Co-FZSM-5, La-FZSM-5, CoLa-FZSM-5) prepared in Example 1 are as follows: Figure 1 shown.

[0049] Depend on Figure 1 It can be seen that the characteristic diffraction peaks of ZSM-5 zeolite are observed at 2θ=7°-9° and 22°-25°, and the typical peaks of the MFI structure are still retained in the catalysts treated with fluoride acidic solution and modified with metal loading, which means that the structure of ZSM-5 is not destroyed after fluoride acidic solution etching and metal loading treatment.

[0050] In addition, since Co(NO3)2 decomposes when calcined in air, Co-FZSM-5 shows a characteristic peak of Co3O4 at 2θ of 36.9°. Similarly, La-FZSM-5 shows a characteristic peak of La2O3 at 2θ of 28.01°. However, the characteristic peaks of these metal oxides are not obvious, which may be because these metals are X-ray amorphous, or the metal oxides are too small, resulting in the nanoparticles being highly dispersed on the surface or inside the pores of the zeolite, or the metal loading is low. It may also be due to the doped metal (Co 2+ ,La 3+ ) was effectively incorporated into the framework of ZSM-5, replacing Al atoms, which resulted in weaker characteristic peaks.

[0051] The relative crystallinity of the catalyst was calculated using the four relatively strong diffraction peaks of the unmodified parent ZSM-5 at 8.0°, 8.8°, 23.1° and 24.0° as comparison standards. Relative crystallinity of FZSM-5, Co-FZSM-5, La-FZSM-5 and CoLa-FZSM-5 were 96.1%, 94.1%, 89.4% and 91.5% respectively relative to ZSM-5 molecular sieve. The results showed that the crystallinity of all modified molecular sieves decreased, with La-FZSM-5 being the lowest, with a relative crystallinity of 89.4%, which means that although the fluoride and metal loading did not change the topological structure of the catalyst, its structural orderliness decreased.

[0052] (2) BET analysis

[0053] The AUTOCHEMⅡ2920 fully automatic chemisorption analyzer produced by Micromeritics of the United States with a thermal conductivity detector (TCD) was used for programmed temperature desorption of ammonia (NH3-TDP) analysis. During the test, about 100 mg of sample was weighed and placed in a reaction tube, and the temperature was programmed to rise from room temperature to 300℃ at 10℃ / min for drying. It was purged with He gas flow (30ml / min) for 1h, cooled to 50℃, and then ammonia gas was introduced to adsorb to saturation, and then switched to He gas flow to purge to remove weakly physically adsorbed NH3 on the surface. The temperature was raised to 750℃ at a rate of 10℃ / min in a He atmosphere for desorption. In this way, the acidity was determined, and the quantification of acid positions can be calculated by Gaussian curve fitting. In addition, the Autosorb-iQ of Quantachrome Instruments US was used for nitrogen adsorption and desorption tests, and the brunauer-emmet-teller (BET) specific surface area and pore volume were calculated by t-plot method.

[0054] The N2 adsorption and analytical isotherms of the zeolite molecular sieve catalysts (ZSM-5, FZSM-5, Co-FZSM-5, La-FZSM-5, CoLa-FZSM-5) prepared in Example 1 are shown in FIG. Figure 2 As shown. Figure 2 It can be seen that the adsorption isotherm of the parent ZSM-5 increases rapidly at a low relative pressure, and then tends to saturation under medium relative pressure conditions, which shows that it has typical type I adsorption isotherm characteristics, indicating that the parent ZSM-5 has microporous characteristics. In contrast, FZSM-5 and metal-modified molecular sieves show mixed isotherms of type I and type IV, and there are adsorption hysteresis loops in the smaller pressure range (near 0.2) and the medium and high pressure range (after 0.5), which indicates that the modified hierarchical molecular sieve (hierarchical ZSM-5) has both micropores and mesopores, representing the characteristics of a hierarchical porous structure. Compared with the parent ZSM-5, the adsorption amount of the molecular sieve after acid treatment increases, indicating that the mesopores are connected along the micropore surface of the crystal, and capillary condensation occurs on the zeolite surface and inside the crystal.

[0055] The sieve size distribution obtained by the BJH method is as follows Figure 3 As shown, the pore sizes of the catalysts are concentrated in the range of 3.5 to 4.5 nm, while the pore size distribution of the molecular sieve treated with the acid solution increases within this range.

[0056] Table 1 summarizes the structural characteristics of each catalyst sample. After acid solution and metal loading treatment, although the BET surface area (S BET ) is reduced, but compared with the parent ZSM-5, the total pore volume (V total ) increases, specifically the mesopore volume (V meso ) increased significantly, but the micropore volume (V micro ) is almost unchanged. The increase in pore volume is mainly due to the removal of cations (aluminum and silicon) in the zeolite framework during acid etching, which leads to the generation of pores. This is particularly evident in the mesopores. It is worth noting that after treatment with fluoride acid solution, the mesopore area (S meso ) from 150.3 to 99.6m 2 / g decreased significantly, while the mesopore volume (V meso ) slightly increased, which can be attributed to the fact that the leaching of acid solution mainly strengthened the existing mesopores (2-10 nm) of zeolite without generating new mesopores. meso ), mesopore volume (V meso ) were greatly reduced, while the micropore surface area (S micro ) increases significantly, and the micropore volume (V micro) also increased slightly, indicating that metal oxides can be loaded into the mesopores, resulting in partial pore blockage. At the same time, metal oxides form metal clusters on the mesopore walls to form micropores, increasing the volume of the micropores. Pore blockage is not conducive to the approach of the reactants to the active sites and the mass transfer of guest molecules. These deficiencies can be improved by acid etching the parent ZSM-5 to increase the mesopore volume.

[0057] Table 1 Structural characteristics of catalysts

[0058]

[0059]

[0060] a Calculated by Multi-point BET method.

[0061] b The total pore volume relative pressure is 0.99.

[0062] c Calculated by t-plot method.

[0063] d Calculated by difference method, S meso =S BET -S micro ,V meso =V total -V micro .

[0064] e Determined by ICP-OES test analysis method.

[0065] (3) Morphological analysis

[0066] ThermoFisher's ApreoC scanning electron microscope (SEM) was used to characterize the morphology of the molecular sieve catalyst samples. All samples were pre-sprayed with an appropriate amount of platinum metal (Pt) before shooting, and the acceleration voltage used for the test was 10KV. The metal-loaded molecular sieves were observed using a FEI Tecnai G2 F30 transmission electron microscope (TEM). At the same time, the device was equipped with an energy-dispersive X-ray spectroscopy (EDS) detector (energy-dispersive X-ray spectroscopy) model EDAX Elite T, which was used to scan and detect the distribution of metal elements in the molecular sieve.

[0067] The SEM image of the untreated parent molecular sieve is as follows Figure 4As shown in (a), it can be seen that the sample is composed of uniform grains and has a typical ZSM-5 morphology. Typical 90° twin symbiosis can be observed on the (010) surface. The XRD test results also show that the zeolite has high X-ray crystallinity and does not contain amorphous matter or other crystalline impurities. Figure 4 (b) is a morphology of the molecular sieve impregnated with a mixed solution of NH4F and HF. It can be seen that the acid corrodes the molecular sieve significantly, and a large number of pore structures appear on its surface. This is because NH4F-HF reacts with silicon and aluminum in the molecular sieve framework. This reaction preferentially dissolves the defective areas of ZSM-5. Once the etching process starts on the crystal surface, the reaction will proceed rapidly and enter the interior of the crystal, which usually leads to restricted etching of the outer surface, and then forms large mesopores and macropores deep into the crystal. These pore structures formed by etching have a positive effect on the landing point of metal loading and the diffusivity of catalytic reactions.

[0068] Figure 4 (c), (d) and (e) are the TEM and energy spectrum images of the molecular sieves after Co, La and CoLa metal loading, respectively. From the images, we can see that the surface of the molecular sieves is covered with black metal oxide particles, which is consistent with the XRD results, confirming the presence of Co3O4 and La2O3 in the catalyst. Although the low loading leads to the agglomeration of metal oxides, the overall dispersion of the metal oxide particles is good, and the active substances have good dispersion, which means that the active sites can be better exposed, which is conducive to the improvement of catalytic activity. It is worth noting that Figure 4 The typical defect structure after acid etching can be seen in the TEM image of (d), and the energy spectrum of silicon and aluminum elements better shows this point. The silicon element is missing, while the aluminum element appears to be aggregated after being separated from the skeleton. This may be related to the corrosion process of NH4F-HF solution. Based on the chemical equilibrium of HF-NH4F-H2O system, HF will ionize H in water. + 、F - and HF2 - HF and HF2 as active substances - It has removal activity for both Al and Si. After properly adjusting the concentrations of HF and NH4F, the framework Al and Si will be released in equal amounts. This plays an important guiding role in the modification and preparation of graded molecular sieves without changing SAR.

[0069] (4) NH3-TPD analysis

[0070] Figure 5 is the NH3-TPD spectrum of each catalyst, Figure 5It can be seen that two NH3 desorption peaks appear at 100-240℃ and 240-450℃, corresponding to the weak acid site and strong acid site of the catalyst respectively. Acid sites, and its analytical peak at low temperature indicates Lewis acid sites. Compared with the parent ZSM-5, the peaks and acid center points of FZSM-5 in the weak acid zone and strong acid zone after acid leaching and stratification tend to be less obvious. In addition, after treatment with NH4F+HF solution, the low-temperature peak and high-temperature peak of the catalyst both moved slightly to the low-temperature zone, indicating that the desiliconization / aluminization of the catalyst led to a decrease in the strength of weak acid sites and strong acid sites. Table 2 lists the acid content and proportion of different types of acids in each catalyst. With the loading of metal, the total acid content of the catalyst is further reduced compared with the acid-leached molecular sieve. This may be due to the incorporation of metals to cover some acid sites, resulting in a further reduction in the total acid content.

[0071] Table 2 Acid amount and proportion of different types of acids in each catalyst

[0072]

[0073] Experiment 2 Thermogravimetric analysis

[0074] In this experiment, typical lignite from Shengli Coal Mine in Xilin Gol League, Inner Mongolia Autonomous Region was selected as the test coal sample. Before the experiment, the coal sample was crushed, ground and sieved to a particle size of less than 0.075 mm. The sieved material was then dried at 105°C for 24 hours and stored in a sealed container for later use. The coal sample was subjected to industrial analysis and elemental analysis according to the Chinese national standard GB / T 212-2008. The analysis results are shown in Table 3.

[0075] Table 3 Industrial analysis and elemental analysis of lignite samples (weight percentage)

[0076]

[0077] Thermogravimetric analysis of the mixture of lignite and molecular sieve catalyst (mechanical convection mixing, weight ratio of 1:1) was performed using a TGDTA7300 thermogravimetric analyzer produced by Hitachi, Japan. The test sample size was about 10 mg, the flow rate of N2 gas under normal pressure was 60 mL / min, the heating rates were 5°C / min, 10°C / min, 20°C / min, 40°C / min, and the final temperature was 700°C. According to the thermogravimetric analysis results of pure ZSM-5 catalyst, the total mass loss of molecular sieve from room temperature to 700°C was less than 0.5%, which is negligible compared with the mass loss of lignite under the same conditions.

[0078] Figure 6 TG curves of pyrolysis of each zeolite molecular sieve catalyst mixed with lignite in a ratio of 1:1. Figure 7The DTG curves of pyrolysis of each zeolite molecular sieve catalyst and lignite mixed in a ratio of 1:1. Figure 6 It can be seen that the catalytic pyrolysis of lignite can be divided into three stages: the first stage is the drying and degassing stage (room temperature to 310°C), which is mainly to remove the moisture in the mixture of lignite and catalyst and the gases such as CO2 and N2 in the pores. The second stage is the release stage of volatiles in the catalytic pyrolysis of lignite (310-600°C). In this stage, as the pyrolysis temperature increases, the organic macromolecular structure in the lignite undergoes depolymerization and decomposition reactions, the lignite softens and decomposes, and begins to precipitate coal gas (CO, CO2 and gaseous hydrocarbons) and tar. The solid product of this stage is semi-coke. The third stage is the further coking stage of semi-coke (>600°C). In this stage, as the pyrolysis temperature continues to increase, the internal pore structure of the semi-coke undergoes condensation and collapse, thermal polycondensation occurs, and the aromatic nucleus is significantly enlarged, the arrangement gradually becomes regular, and the true density increases. In this stage, the amount of tar precipitated is small, but the amount of CH4 and H2 generated increases significantly, which leads to a continued increase in the weight loss rate. It is worth noting that in the first stage, the weight loss rate of the mixed sample of lignite and ZSM-5 is higher than that of other samples. When the temperature reaches 310℃, the weight loss rate reaches 2.29%, while the weight loss rates of other samples at the same temperature are between 1.58% and 1.79%, which may be related to the pore structure of the catalyst. As shown in Table 1, the S of ZSM-5 BET The higher specific surface area means a greater adsorption of moisture and gas in the air at the same temperature and pressure. Figure 2 This also proves that the adsorption capacity (gas and water) of ZSM-5 under low pressure is greater than that of other catalysts. Therefore, when the pyrolysis temperature of lignite and ZSM-5 reaches 310℃, the water and gas released by the mixture of lignite and metal-supported catalyst is more, and the weight loss rate is greater. In the second stage, the weight loss curve of the mixture of lignite and metal-supported catalyst drops significantly, and the metal-supported catalyst promotes the pyrolysis of lignite. Figure 6It can be seen that when the pyrolysis temperature reaches 600℃, the weight loss rate of the mixed sample of lignite and FZSM-5 is the smallest (13.75%), which is less than the weight loss rate of the mixed sample of lignite and ZSM-5. This may be related to the activity of the catalyst. FZSM-5 is etched by the acid solution, removing Si and Al in the skeleton, resulting in a decrease in its acid sites, thereby reducing its catalytic activity (see Table 2). At 600℃, the weight loss rate of the mixed sample of the metal-supported catalyst and lignite is greater than that of the mixed sample of ZSM-5. This is because with the addition of active metals, the activity of the catalyst is enhanced, thereby promoting the pyrolysis of lignite, and the promotion effect of the bimetallic catalyst CoLa-FZSM-5 is better than that of the single metal catalysts Co-FZSM-5 and La-FZSM-5. When the temperature exceeds 600℃, as the pyrolysis temperature continues to rise, the weight loss rate of each group of samples continues to increase, and the promotion effect of La-FZSM-5 weakens. The weight loss rate of the mixed sample with lignite at the final reaction temperature of 725℃ is less than that of Co-type catalyst and CoLa-type catalyst, indicating that Co-FZSM-5 has a stronger catalytic performance than La-FZSM-5 in promoting the polycondensation reaction of pyrolysis semi-coke, and the catalytic ability of the bimetallic supported catalyst for polycondensation reaction is better than that of the single metal catalyst. Figure 7 From the DTG curves, it can be seen that the maximum weight loss rate peaks of Co, La and CoLa supported catalysts all slightly shifted to the low temperature zone, which indicates that the addition of metal catalysts reduces the activation energy of the light fragments that form volatiles in the coal macromolecular structure, thereby promoting the maximum weight loss rate peak to move to the low temperature zone. Figure 7 Among them, the maximum weight loss rates of all samples are CoLa-FZSM-5>Co-FZSM-5>La-FZSM-5>FZSM-5>ZSM-5, which indicates that metal-supported catalysts have a stronger promoting effect on coal pyrolysis. In addition, due to the more developed mesopores of FZSM-5, the mass transfer effect on the decomposition and volatilization of the intrinsic mineral crystal water contained in lignite is better, resulting in the maximum weight loss rate of lignite catalyzed by FZSM-5 being greater than the maximum weight loss rate of the mixed sample of ZSM-5 and lignite.

[0079] Figure 8 TG curves and DTG curves of non-catalytic pyrolysis of lignite at different heating rates (5, 10, 20 and 40 °C / min), Fig. 9 DTG curves of lignite catalytic pyrolysis at different heating rates (5, 10, 20 and 40 °C / min) (the catalyst in the catalytic reaction is CoLa-FZSM-5, the same below). Figure 8 , Fig. 9 It can be seen that the catalytic and non-catalytic pyrolysis process of lignite can be divided into three stages, namely, the drying and degassing stage (room temperature to 310 °C), the lignite catalytic pyrolysis volatile matter release stage (310-600 °C) and the semi-coke further coking stage (>600 °C), which is consistent with the Figure 6 , Figure 7The results are consistent. Figure 8 , Fig. 9 From the DTG curve, we can see that the maximum weight loss rate of lignite pyrolysis occurs at about 450°C. This is mainly because when the pyrolysis temperature reaches about 450°C, the oxide mineral quartz contained in the lignite and the crystal water in kaolinite (2SiO2·4Al2O3·4H2O) decompose, causing the coal sample to have the maximum weight loss rate at this temperature. Compared with non-catalytic pyrolysis, the peak value of the DTG curve of catalytic pyrolysis is smaller, indicating that the presence of CoLa-FZSM-5 is conducive to the pyrolysis of lignite. Figure 8 , Fig. 9 It can be seen that with the increase of pyrolysis heating rate, both TG and DTG curves move to the high temperature zone. This is because there is a temperature difference between the inside and the surface of the coal sample, which produces a heat transfer lag effect, making the pyrolysis reaction rate inside the coal particles lower than that on the surface of the coal particles. Fig. 9 It can be seen that compared with non-catalytic pyrolysis, under the action of CoLa-FZSM-5 catalyst, the temperature range corresponding to the DTG curve peak of lignite pyrolysis shifts slightly to the left, which indicates that the addition of CoLa-FZSM-5 reduces the activation energy of light fragment breakage that forms volatiles in the lignite macromolecular structure.

[0080] Experiment 3: Product Analysis

[0081] The products of lignite pyrolysis catalyzed by ZSM-5, FZSM-5, Co-FZSM-5, La-FZSM-5 and CoLa-FZSM-5 were analyzed by Py-GC / MS coupling system [Multi-Shot pyrolyzer (EGA / PY-3030D) Frontier Laboratories Ltd. and GCMS-QP2020NX gas chromatograph-mass spectrometer, Shimadzu Coporation]. The catalyst and coal sample were mixed in a weight ratio of 1:1, and the mixing process adopted mechanical convection mixing method. Chromatographic separation was performed using a J&W 122-5532DB-5ms capillary column (30m×0.25mm×0.25μm) with an injection split ratio of 50:1. The temperature was raised from room temperature to 40°C for 3 min at a heating rate of 10°C / min, then raised to 180°C for 5 min at the same heating rate, and finally raised to 300°C for 1 min. The injection port temperature was 250°C. The carrier gas was helium (99.999%) with a flow rate of 1mL / min. The ion source was an EI source of 70eV, the injection and transmission temperature was 250°C, and the mass spectrometry data were collected in the scanning range of m / z 2 to 500. Pyrolysis compounds The compounds in the chromatogram were identified from the NIST and F-Search pyrolysis libraries, and then the abundance of each generated substance was determined by integrating the area under each scan peak and the SIM mode.

[0082] The components of the pyrolysis products were analyzed by Py-GC / MS to confirm the status of various substances therein. Fig.10 The effects of various zeolite molecular sieve catalysts on the selectivity of lignite pyrolysis products are shown, where (a) is the ion chromatogram of the Py-GCMS product. Fig.10 (a) shows the effect of different catalysts on the proportion of different volatile products during lignite catalytic pyrolysis. Fig.10 As shown in (b), the BTEXN yield of lignite catalytic pyrolysis under different catalyst conditions is as follows Fig.10 (c) As shown in 10(b), the tar components can be classified into aliphatic, phenolic, monocyclic aromatic hydrocarbons, polycyclic aromatic hydrocarbons, acids, ketones, aldehydes and other components after a detailed analysis. Under various catalytic conditions, the tar produced by lignite pyrolysis is mainly composed of aliphatic, aromatic and phenolic compounds. Among them, under the pyrolysis conditions of metal-supported catalysts, the content of light oxygen-containing compounds (such as phenols, ketones and aldehydes) in the pyrolysis tar decreases, while the content of aromatic compounds [monocyclic aromatic hydrocarbons (MAHs) and polycyclic aromatic hydrocarbons (PAHs)] increases. This is because under the catalytic action of Co and La, light oxygen-containing compounds undergo deoxygenation reactions (including decarbonylation and decarboxylation reactions) to generate small molecular hydrocarbon compounds, which are further cyclized to generate aromatic hydrocarbons under the hydrogen transfer and aromatization of Co and La-supported FZSM-5 catalysts. In addition, Co and La metal catalysts also have efficient acid-catalyzed cracking ability for aliphatic hydrocarbon compounds, which breaks long-chain hydrocarbons into small molecule olefins or alkanes, which further increases the production of aromatic hydrocarbons. However, after catalytic pyrolysis of FZSM-5, the relative contents of aliphatic hydrocarbons and phenols increased, while the content of aromatic hydrocarbons decreased, which may be related to the etching of the catalyst by fluoride acid solution. Acid reduction.

[0083] Depend on Fig.10(c) It can be seen that the total BTEXN yield of lignite pyrolysis under different catalytic conditions is between 19.29 and 28.53 mg / g. Among them, the BTEXN yield of lignite pyrolysis tar catalyzed by FZSM-5 is the lowest (19.29 mg / g). This is because the crystal particles of FZSM-5 are more amorphous after being etched by fluoride acid solution, and there are more MFI skeleton structure defects. Its acid content is significantly lower than that of other catalysts. The strong acid sites on the surface of ZSM-5 catalyst can induce the polarization of CH bonds of volatiles and the dehydrogenation of saturated hydrocarbons, so that they are reformed into precursors of aromatic compounds. The reduction of acid sites means that the aromatization process is limited, thereby reducing the yield of light aromatics. Compared with ZSM-5 catalytic pyrolysis, the BTEXN yield of lignite pyrolysis increases with the addition of Co and La metals, which shows that the metal-loaded catalyst has better aromatization and deoxygenation performance of olefins and alkanes, resulting in the production of more AHs. For single metal supported catalysts, the catalytic pyrolysis of Co-FZSM-5 mainly promoted the formation of benzene and toluene. The yields of ethylbenzene and xylene in the catalytic pyrolysis products of La-FZSM-5 increased significantly. The bimetallic supported CoLa-FZSM-5 catalyst further increased the yields of benzene, ethylbenzene and xylene (6.91% and 10.39% higher than Co-FZSM-5 and La-FZSM-5, respectively). These results show that single metal and bimetallic composite catalysts have strong selectivity and catalytic performance for certain specific products. The enhancement of aromatic selectivity may be due to the additional hydrodeoxygenation activity induced by the Co or La metal active sites. Among them, Co-FZSM-5 is more conducive to the formation of BTEXN, especially the formation of benzene and toluene. It is worth noting that when the total metal loading remains unchanged, the composite loading mode of metal Co and La shows an additive effect. When CoLa-FZSM-5 is used for catalytic pyrolysis, it has more obvious advantages in the production of light aromatics than single metal loading, and the recovery rate of BTEXN is higher. The presence of two metals can improve the overall activity of bimetallic catalysts by promoting the dispersion of metal oxides in the catalyst and enhancing the hydrogenation reaction. In addition, the electronic effect between the two metals in the bimetallic catalyst is an important factor in improving its catalytic performance, promoting its selectivity for aromatic compounds.

[0084] Experiment 4 Kinetic Analysis

[0085] The reaction rate of lignite pyrolysis can be defined by formula (1):

[0086]

[0087] Where a is the conversion rate, which can be calculated by formula (2); k(T) is the reaction rate constant; t is the reaction time; and f(a) is the kinetic mechanism function.

[0088]

[0089] In the formula, m i is the initial mass of the coal sample; m t is the mass of the coal sample at time t; m f is the mass of the final coal sample.

[0090] Generally, k(T) can be expressed as formula (3) using the first-order reaction model in the Arrhenius equation:

[0091]

[0092] Where E is the activation energy (kJ mol -1 ); R is the molar gas constant (8.314×10 -3 kJ mol -1 K -1 ); T is the absolute temperature (K); A is the pre-exponential factor.

[0093] Under non-isothermal conditions, the constant heating rate β can be expressed by formula (4) as:

[0094]

[0095] Therefore, under non-isothermal and heterogeneous conditions, the coal pyrolysis kinetic equation can be expressed by formula (5) as follows:

[0096]

[0097] The calculation process of kinetic analysis is as follows Fig.11 As shown, the kinetic analysis can be divided into three parts: using various isoconversion rate methods to determine the activation energy; using the Kissinger method to calculate the pre-exponential factor; and using the Master plots method to determine the most probable kinetic mechanism function f(α).

[0098] (1) Activation energy

[0099] Four isoconversional methods in differential or integral form, namely Friedman method, Starink method, KAS method (Kissinger-Akahira-Sunose) and FWO method (Flynn-Wall-Ozawa), are used to calculate the activation energy (Eα) of the entire reaction process. These four methods are commonly used in the pyrolysis reaction process. All these methods follow a principle, that is, to determine the temperature at which the equivalent reaction stage is reached at different heating rates to calculate the activation energy. Among them, the Friedman method belongs to the differential method, and the other three belong to the integral method. The Friedman method is based on experimental data and does not make any assumptions or simplifications, so it is the most reliable, but it is very sensitive to experimental conditions. The Starink, KAS and FWO methods use rate equations in integral form and use various mathematical approximations, such as Doyle, Murray & White, etc., so they are more prone to errors. Using the above four models to calculate the activation energy can improve the credibility of the results. The calculation formula of the isoconversion method is as follows:

[0100] Friedman method:

[0101]

[0102] Among them, at different conversion rates and heating rates, ln(dα / dt) α,i and (1 / T α,i ) is (-E α / R), the activation energy can be calculated by the slope, and ln[f(a)A α ] is the intercept.

[0103] Starink method:

[0104]

[0105] Where, β represents the heating rate (K / min), ln(β i / T 1.92 α,i ) and (1 / T α,i ) is (-1.0008E α / R), the corresponding activation energy can be calculated by the slope.

[0106] KAS method:

[0107]

[0108] Where, β represents the heating rate (K / min), ln(β i / T 2 α,i ) and (1 / Tα,i ) is (-E α / R), the corresponding activation energy can be calculated by the slope.

[0109] FWO Law:

[0110]

[0111] Where, β represents the heating rate (K / min), ln(β i ) and (1 / T α,i ) is (-0.457E α / R), the corresponding activation energy can be calculated by the slope.

[0112] Fig.12 The fitted straight lines of the kinetics of catalytic and non-catalytic pyrolysis of lignite calculated by four equal conversion rate methods: Starink, Friedman, FWO and KAS. (a), (b), (c) and (d) are non-catalytic pyrolysis (Starink, Friedman, FWO and KAS, respectively); (e), (f), (g) and (h) are catalytic pyrolysis of CoLa-FZSM-5 (Starink, Friedman, FWO and KAS, respectively). The thermogravimetric curves with heating rates of 5℃ / min, 10℃ / min, 20℃ / min and 40℃ / min were used as calculation data, and the conversion rate α was taken in the range of 0.20 to 0.90 at intervals of 0.05 for plotting. The equal conversion rate curves change with the change of conversion rate α. The slopes of these fitted straight lines are used to calculate the activation energy E. The correlation coefficient (R 2 ) Most of them are within the range of 97% to 99%, and the linear correlation is high, indicating that the activation energy results obtained are accurate and reliable. The activation energy results calculated by the four models of Starink, Friedman, FWO and KAS are similar. Through the mutual verification of these four models, it can be proved that the results obtained are reliable.

[0113] Fig.13 Activation energy calculated for Starink, Friedman, FWO and KAS models as a function of conversion. Fig.13It can be seen that within the range of lignite pyrolysis conversion rate of 0.2 to 0.9, the change in activation energy of pyrolysis reaction can be divided into two stages. The activation energy range of the first stage of non-catalytic pyrolysis is 198.70 to 232.23 kJ / mol (α = 0.2 to 0.75), and the activation energy range of the second stage is 223.97 to 248.68 kJ / mol (α = 0.0.75 to 0.9). The activation energy range of the first stage of catalytic pyrolysis is 174.87 to 216.23 kJ / mol (α = 0.2 to 0.75), and the activation energy range of the second stage is 228.82 to 279.09 kJ / mol (α = 0.75 to 0.9). In general, the activation energy of lignite pyrolysis and catalytic pyrolysis gradually increases with the increase of conversion rate. The activation energy of catalytic pyrolysis is generally lower than that of non-catalytic pyrolysis, indicating that the addition of CoLa-FZSM-5 catalyst reduces the activation energy of pyrolysis reaction. It is generally believed that the activation energy of the pyrolysis reaction is related to the concentration of activated molecules and the strength of their chemical bonds during the reaction. In the first stage of lignite pyrolysis, water and gas have been precipitated. As the conversion rate increases, the organic macromolecular structure in the lignite is depolymerized and decomposed, and volatile substances are gradually precipitated, and the activation energy of the reaction gradually increases. The reduction in activation energy after adding a catalyst may be due to the fact that the acid sites (Brühl and Lewis) and metal activity in the CoLa-FZSM-5 catalyst increase the rates of cracking, decarbonylation, deoxygenation, and ring-opening reactions, which promote the degradation of lignite organic matter. In addition, the rich pore size of the catalyst at the beginning of the reaction also improves the mass transfer of the reaction substances, further reducing the activation energy of the reaction. In the second stage of lignite pyrolysis, as the conversion rate increases, the hydrogenated aromatic clusters and aliphatic groups of the coal are dehydrogenated, and the condensation and cross-linking of coke require more energy to excite, so the activation energy of the reaction gradually increases. It is worth noting that in the second stage, the activation energy of catalytic pyrolysis is greater than that of non-catalytic pyrolysis. This may be due to the accumulation of coke in the pores inside the catalyst, which causes the catalyst to hinder the mass transfer process of the reaction and thus increase the activation energy of the pyrolysis reaction.

[0114] (2) Pre-exponential factor

[0115] Although isoconversion methods can provide activation energy values ​​very accurately, they cannot derive reaction models for pre-exponential or solid-state reactions. Kissinger is not an isoconversion method, but is considered to be very close to the isoconversion method and can be used to calculate pre-exponential factors. The Kissinger model can be expressed by formula (10):

[0116]

[0117] Among them, T m It is the peak temperature of the DTG curve or the temperature at maximum conversion rate.

[0118] The Kissinger model can only give a single activation energy value for the entire reaction process, so it is not used to calculate the activation energy. However, if the activation energy value at each conversion rate is known, the pre-exponential factor can be calculated. Extracting A from formula (10) and rearranging it yields:

[0119]

[0120] Based on the average activation energy at each conversion rate calculated by the four equal conversion rate methods, the corresponding pre-exponential factor A at each rate can be obtained using formula (11).

[0121] Table 4 shows the pre-exponential factors at heating rates of 5, 10, 20 and 40 °C / min. The pre-exponential factors are calculated by Starink, Friedman and FWO to obtain the average activation energy, and then the activation energy value is substituted into the Kissinger formula. It can be seen from the table that when the heating rate is 5, 10, 20 and 40 °C / min, the non-catalytic pre-exponential factor A α The range is 4.96×10 8 ~1.41×10 12 min -1 , and the pre-exponential factor A of catalytic pyrolysis α The range is 3.13×10 7 ~2.08×10 12 min -1 . The numerical value of the pre-exponential factor can be explained by collision theory. Generally, the higher the value of the pre-exponential factor, the higher the molecular collision rate required for the pyrolysis reaction. The pre-exponential factor of lignite pyrolysis has a large variation range, which illustrates the complexity of the lignite pyrolysis reaction. In the later stage of the reaction (α>0.8), the increase in the pre-exponential factor indicates that the pyrolysis reaction is slow and difficult at this stage. In addition, it can be seen from Table 4 that the pre-exponential factor increases with the increase of the heating rate, which shows the correlation between the pre-exponential factor A and the heating rate. This is because a high heating rate will increase the frequency and intensity of collisions between molecules. Therefore, the higher the heating rate, the higher the pre-exponential factor of the reaction.

[0122] Table 4 Pre-exponential factors at heating rates of 5, 10, 20 and 40 °C / min

[0123]

[0124] (3) Reaction model

[0125] The reaction mechanism model f(α) can be predicted using the Z(α) master plot method. The master plot method is based on the reaction activation energy E and is independent of the conversion rate α. First, the reaction activation energy E is estimated using the equal conversion method, and then the E value is used to calculate the function Z(α). The generated experimental curve is then compared with the standard reaction model curve based on diffusion, geometrical construction, nucleation, order etc., and the most probable mechanism model f(α) is determined based on the curve coincidence or trend. Table 5 shows different models based on solid-state kinetics and their integral and differential forms.

[0126] Formula (12) is a simplified formula of the main graph equation Z(α):

[0127]

[0128] Among them, f(α) and G(α) are integral and differential forms respectively, (dα / dt) 0.5 and T 0.5 They are the reaction rate and temperature when α=0.5. According to the theoretical curve And the experimental curve The most probable mechanism function f(α) can be determined by changing α.

[0129] Table 5 Different models based on solid-state dynamics and their integral and differential forms

[0130]

[0131] Fig.14 The experimental curve and standard curve of non-catalytic pyrolysis and catalytic pyrolysis of lignite determined by the main graph method. To predict the reaction model, TG data with a heating rate of 20℃ / min are used, and the theoretical model is shown in Table 5. Fig.14 It can be seen that when the conversion rate is less than 0.15, the experimental curve basically coincides with the P2 / 3 theoretical curve. However, when the conversion rate is greater than 0.2, the experimental curve is inconsistent with any theoretical main graph. This trend illustrates the complexity of low-rank lignite pyrolysis, which usually involves many series, parallel and competing reactions. Fig.14 It can be seen that when the conversion rate is 0.2 to 0.8, the experimental curve and the standard curve R6 have the same change trend. R6 belongs to the simple series reaction model, and the corresponding integral mechanism function is G(α)=[(1-α) 1-n -1] / (n-1), the experimental curve does not completely overlap with the standard curve, indicating that the integer n cannot be used to describe the kinetic mechanism. In fact, lignite pyrolysis follows very complex kinetics, which also makes it very difficult to accurately predict the model.

[0132] From the above results, the existing reaction model cannot describe the reaction process of the main stage. Therefore, the present invention uses the empirical formula proposed by Sestak and Berggren to construct the reaction mechanism function of the main reaction stage (α = 0.12-0.8) of low-rank lignite pyrolysis and catalytic pyrolysis. The Sestak and Berggren empirical formula is shown in formula (13).

[0133] f(α)=(1-α) n ×α m [-ln(1-α)] p (13);

[0134] Among them, n, m and p are dynamic empirical fitting parameters. By combining formula (5) and formula (13), we can get:

[0135]

[0136] In Microsoft Office Excel Solver, the generalized reduced gradient (GRG) algorithm is used to minimize the objective function OF [Formula (15)], and the reaction order of Formula (14) at each heating rate can be estimated, that is, the unknown parameters n, m and p of the Sestak and Berggren formula. The calculation results are shown in Table 6.

[0137]

[0138] Table 6 SB model parameters obtained after optimizing equations

[0139]

[0140] In order to more accurately describe the pyrolysis reaction mechanism, the average values ​​of n, m and p obtained by solving multiple heating rates are used to construct the model. Therefore, according to the results in Table 6, the most probable mechanism functions of non-catalytic and catalytic pyrolysis of low-rank lignite are shown in formulas (16) and (17), respectively.

[0141] f(α)=(1-α) -1.82 ×α 4.21 [-ln(1-α)] -4.17 (16);

[0142] f(α)=(1-α) -1.64 ×α 5.33 [-ln(1-α)] -4.32 (17);

[0143] The parameters n, m and p represent the diffusion, reaction order and nucleation mechanism respectively.

[0144] From formulas (16) and (17), we can see that the n-value order of lignite pyrolysis and non-catalytic pyrolysis is the smallest, indicating that the diffusion model has little influence on lignite pyrolysis and catalytic pyrolysis. The values ​​of the reaction order m are relatively large, 4.21 and 5.33 respectively, indicating that the reaction order model can be used as the main mechanism model of lignite pyrolysis, which is consistent with Fig.14 The experimental curve trend is consistent. The nucleation mechanism model values ​​P are -4.17 and -4.32, respectively, indicating that this process also has an important influence on the pyrolysis of lignite. In addition, compared with non-catalytic pyrolysis, the most probable mechanism functions m and p orders of catalytic pyrolysis increase, indicating that the influence of reaction order and nucleation mechanism on the catalytic pyrolysis of lignite increases. In general, the pyrolysis and catalytic pyrolysis processes of lignite initially follow the nucleation model P3 / 4 (α<0.15), and gradually transform into reaction order and nucleation mode with the increase of conversion rate. It should be noted that the SB model equation provides a broad mathematical framework for describing lignite pyrolysis and catalytic pyrolysis, and its results should not be regarded as specific kinetic equations.

[0145] Experiment 5 Mechanical Hypothesis

[0146] HF and NH4F mixed acid solution etching and metal loading ZSM-5 process Fig.15 As shown, in order to gain a deeper understanding of the structural changes of the molecular sieve and the production process of BTEXN. The promotion of the pyrolysis process by ZSM-5 molecular sieve mainly depends on the accessibility of the metal sites of the acidic sites, so as to achieve the best balance between the pores and the acidic sites. It is well known that ZSM-5 contains abundant microporous systems, but lacks mesoporous systems that are conducive to mass transfer. If ZSM-5 is not treated and metal is directly loaded, although some of the external The acid sites are easily blocked by micropores, which is not conducive to the reactants entering the molecular sieve and contacting with the active acid sites to form aromatics. In addition, pore blockage is an important reason for the carbon deposition and deactivation of molecular sieves. After HF+NH4F impregnation, the removal of framework aluminum not only reduces the acidity (mainly The presence of a large number of mesopores in FZSM-5 allows the loaded metal particles to enter the pores and avoid aggregation on the catalyst surface. The protons are fixed by interaction. Therefore, the introduction of metal Co and La leads to A large reduction in acid sites. The highly dispersed metal active sites first promote the further cracking of volatiles, and the intermediate molecular substances will enter the pores of the molecular sieve. These substances are called "hydrocarbon pools". These molecules will further undergo various reactions (oligomerization, Diels-Alder cyclization and dehydrogenation aromatization) to form aromatic hydrocarbons. In addition, the further cracking of macromolecular oxygen-containing substances avoids their polycondensation to form coke, which effectively prevents the deactivation of the catalyst caused by carbon deposition. Therefore, CoLa-FZSM-5 has excellent performance in promoting the formation of aromatic hydrocarbons and inhibiting carbon deposition.

[0147] Based on the above experimental studies, the present invention discusses the selectivity of aromatics in the catalytic pyrolysis of lignite over fluoride-modified ZSM-5 and Co, La and bimetallic Co-La-loaded FZSM-5 catalysts and the kinetics of the pyrolysis process. The main conclusions of this study can be summarized as follows:

[0148] (1) Compared with the parent ZSM-5, all modified molecular sieves maintain the MFI crystal structure. After treatment with a mixed acidic solution of HF and NH4F, FZSM-5 exhibits an optimized pore structure. Compared with the parent ZSM-5, the mesopore and micropore volumes of FZSM-5 are increased, which provides a favorable carrier environment for the metal particles to enter the molecular sieve pores for drop point regulation and acid position control.

[0149] (2) Thermogravimetric tests show that the process of lignite catalytic pyrolysis can be divided into three stages, namely, the drying and degassing stage (room temperature to 310°C), the volatile matter release stage (310-600°C) and the further coking stage of semi-coke (>600°C). All metal-supported catalysts shift the peak of the maximum weight loss rate toward the low temperature direction compared with FZSM-5 and ZSM-5, indicating that the metal catalyst further reduces the activation energy required for the light fragments in the coal molecular structure to form volatiles. Among them, CoLa-FZSM-5 has the most significant effect, which is attributed to its more developed mesoporous structure and metal activity, which improves the mass transfer efficiency during lignite pyrolysis.

[0150] (3) Py-GC / MS experiments showed that compared with ZSM-5, metal-supported catalysts can effectively improve the yield of light aromatics (BTEXN) in the pyrolysis of lignite. Specifically, the Co-FZSM-5 and La-FZSM-5 monometallic catalysts mainly promoted the production of benzene, toluene, ethylbenzene and xylene, while the CoLa-FZSM-5 bimetallic catalyst further improved the yield of these aromatics, showing better catalytic performance and aromatics selectivity. This enhanced selectivity is attributed to the additional hydrodeoxygenation activity induced by the metal active sites and the possible electronic effect between the two metals, which together promote the dispersion of metal oxides in the catalyst and the hydrogenation reaction, thereby improving the overall activity of the catalyst. In addition, compared with ZSM-5 without fluoride modification, FZSM-5 has a lower aromatics yield due to the reduction of acidic sites, but the activity of the catalyst is enhanced after metal loading, thereby improving the production of aromatics.

[0151] (4) Kinetic analysis shows that compared with non-catalytic pyrolysis, the addition of CoLa-FZSM-5 helps to reduce the activation energy of lignite pyrolysis. However, in the later stage of the reaction (α>0.75), as the formation of coke inside the molecular sieve leads to an increase in mass transfer resistance, catalytic pyrolysis increases the activation energy of the reaction compared with non-catalytic pyrolysis. The reaction mechanism function was further determined using the main graph method. The mechanism function of lignite non-catalytic pyrolysis is f(α)=(1-α) -1.82 ×α 4.21 [-ln(1-α)] -4.17 , the catalytic pyrolysis mechanism function is f(α)=(1-α) -1.64 ×α 5.33 [-ln(1-α)] -4.32 When the conversion rate α is less than 0.15, the lignite pyrolysis process follows the nucleation model. With the increase of the conversion rate, the lignite pyrolysis process follows the reaction order and nucleation model.

[0152] The above examples are provided to those skilled in the art to fully disclose and describe how to make and use the claimed embodiments, and are not intended to limit the scope of the disclosure herein. Modifications that are obvious to those skilled in the art will fall within the scope of the appended claims.

Claims

1. A method for preparing a bimetallic supported CoLa-FZSM-5 catalyst, characterized in that: The following steps are involved: (1) Dispersing ZSM-5 molecular sieve into an acidic etching solution, stirring at room temperature until it becomes a paste, rinsing with deionized water until it becomes neutral, and controlling the water; then placing the molecular sieve in a muffle furnace, heating it to 540-560° C. at a heating rate of 4-6° C. / min in an air environment and maintaining it for 1.5-2.5 h, cooling and drying to obtain FZSM-5; The acidic etching solution is composed of an HF aqueous solution and NH4F dissolved therein, wherein the concentration of the HF aqueous solution is 0.4-0.6 mol / L, and the concentration of NH4F is 130-200 g / L; (2) FZSM-5 is added to the mixed solution, stirred at 35-45° C. for 2.5-3.5 h, and immersed in a dry state until the water is completely evaporated to obtain a dry solid; then placed in a muffle furnace, calcined at 580-620° C. in an air environment for 3-5 h, cooled and dried to obtain a bimetallic supported CoLa-FZSM-5 catalyst, wherein the loading amount of Co is 1%-10%, and the loading amount of La is 1%-10%; the mixed solution is composed of Co(NO3)2·6H2O, La(NO3)3·6H2O and water.

2. The method for preparing the bimetallic supported CoLa-FZSM-5 catalyst according to claim 1, characterized in that: In the step (1), the ZSM-5 molecular sieve is pretreated as follows: the ZSM-5 molecular sieve is placed in a muffle furnace, calcined at 580-620° C. for 3-5 hours in an air environment, cooled, and dried.

3. The method for preparing the bimetallic supported CoLa-FZSM-5 catalyst according to claim 1, characterized in that: In the step (1), the SiO2 / Al2O3 ratio of the ZSM-5 molecular sieve is 25.

4. The method for preparing the bimetallic supported CoLa-FZSM-5 catalyst according to claim 1, characterized in that: In the step (1), the concentration of the HF aqueous solution is 0.5 mol / L, and the concentration of NH4F is 166.7 g / L.

5. The method for preparing the bimetallic supported CoLa-FZSM-5 catalyst according to claim 1, characterized in that: In the step (1), the temperature is increased to 550° C. at a heating rate of 5° C. / min and maintained for 2 h.

6. The method for preparing the bimetallic supported CoLa-FZSM-5 catalyst according to claim 1, characterized in that: In the step (2), FZSM-5 is added to the mixed solution, stirred at 40°C for 3 hours, and then immersed at 105°C in a dry state until the water is completely evaporated to obtain a dry solid; then placed in a muffle furnace and calcined at 600°C for 4 hours in an air environment.

7. The method for preparing the bimetallic supported CoLa-FZSM-5 catalyst according to claim 1, characterized in that: In the step (2), the loading amount of Co is 3% to 5%, and the loading amount of La is 3% to 5%.

8. A bimetallic supported CoLa-FZSM-5 catalyst prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the bimetallic supported CoLa-FZSM-5 catalyst according to claim 8 in catalyzing the pyrolysis of lignite, or in increasing the yield of light aromatics during the pyrolysis of lignite.

10. The use according to claim 9, characterized in that: The light aromatic hydrocarbons are selected from any one or more of benzene, ethylbenzene and xylene.